2016
DOI: 10.1038/srep35252
|View full text |Cite
|
Sign up to set email alerts
|

Core-shell Au-Pd nanoparticles as cathode catalysts for microbial fuel cell applications

Abstract: Bimetallic nanoparticles with core-shell structures usually display enhanced catalytic properties due to the lattice strain created between the core and shell regions. In this study, we demonstrate the application of bimetallic Au-Pd nanoparticles with an Au core and a thin Pd shell as cathode catalysts in microbial fuel cells, which represent a promising technology for wastewater treatment, while directly generating electrical energy. In specific, in comparison with the hollow structured Pt nanoparticles, a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Pd–Au alloyed catalysts have proved to be excellent catalysts for a number of chemical processes such as the acetoxylation of ethylene to vinyl acetate [12, 20], solvent-free oxidation of primary alcohols to aldehydes [21] and direct synthesis of H 2 O 2 from H 2 and O 2 [22]. Recently, it has been demonstrated that Au-core Pd-shell NPs in microbial fuel cells exhibit enhanced catalytic activity in wastewater treatment technology [23].…”
Section: Introductionmentioning
confidence: 99%
“…Pd–Au alloyed catalysts have proved to be excellent catalysts for a number of chemical processes such as the acetoxylation of ethylene to vinyl acetate [12, 20], solvent-free oxidation of primary alcohols to aldehydes [21] and direct synthesis of H 2 O 2 from H 2 and O 2 [22]. Recently, it has been demonstrated that Au-core Pd-shell NPs in microbial fuel cells exhibit enhanced catalytic activity in wastewater treatment technology [23].…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 5 shows representative EDX line scans images, it can be seen in both NPs scanned that they are composed mainly of molybdenum and some oxygen, and the elemental distribution may correspond to a core-shell type NS [45,46], in which the core is made of metallic molybdenum shown with a blue line in the spectra, and it is surrounded by molybdenum oxide which corresponds to the superposition of blue and green lines in the spectra, as proposed in Ref. [30].…”
Section: Tem-edx Images Of the Mo Npsmentioning
confidence: 77%
“…Yang et al. investigated the application of core‐shell Au‐Pd nanoparticles as a cathodic electrocatalyst in microbial fuel cells, and estimated 16 W m −3 of maximum power density . Modibedi et al.…”
Section: Resultsmentioning
confidence: 99%